ADVANCED AIR MOBILITY (AAM) - Baltazar, Maria Emília (2025)
Nowadays, air taxis are an increasingly materialized reality. Soon companies such as the German Lilium and Volocopter will present their services for moving passengers and goods between notable points in cities, flying over the skies of urban centers. This new electric aviation, dubbed Advanced Air Mobility (AAM), is a reality that is already being prepared in several cities around the world, through implementation plans in Japan, China, Brazil and the USA. This implementation of this new aerial technology of great complexity, which depends on the development and maturity of an Ecosystem, made up of the alignment of several stakeholders, coordinating infrastructures, operations, regulations and communications. The study aims to create a universal tool for characterizing an AAM Ecosystem, as a basis for implementation in any city, region or country, providing support for the development of a ROADMAP that promotes the launch of EVTOL operations. Finally, this work proposes to use this developed tool and promote the Roadmap for the Portuguese case, in order to guide the effective implementation of this new emerging form of air mobility in Portugal.